Neurons and objects: the case of auditory cortex - Nelken, Israel; Bar-Yosef, Omer (Frontiers in Neuroscience, 2008)
Sounds are encoded into electrical activity in the inner ear, where they are represented (roughly) as patterns of energy in narrow frequency bands. However, sounds are perceived in terms of their high-order properties. It is generally believed that this transformation is performed along the auditory hierarchy, with low-level physical cues computed at early stages of the auditory system and high-level abstract qualities at high-order cortical areas. The functional position of primary auditory cortex (A1) in this scheme is unclear – is it ‘early’, encoding physical cues, or is it ‘late’, encoding already abstract qualitiesµ Here we argue that neurons in cat A1 already show sensitivity to high-level features of sounds. In particular, these neurons may already show sensitivity to ‘auditory objects’. The evidence for this claim comes from studies in which individual sounds are presented singly and in mixtures. Many neurons in cat A1 respond to mixtures in the same way they respond to one of the individual members in the mixture, and in many cases neurons may respond to a low-level component of the mixture rather than to the acoustically dominant one, even though the same neurons respond to the acoustically-dominant component when presented alone.